Impact Study on the Implementation of CAL-DEFLL’s Research Writing, Editing, Proofreading, and Orientation on Layout Tools for Publication Purposes Training 2023-2024 - Quintos, Sherrilyn (Social Sciences and Development Review, 2024)
This study investigates the positive impact of extensive training in research writing, editing, proofreading, and publication layout tools on educators’ skills and career advancement. The findings reveal significant improvements in participants’ research writing abilities and confidence in the editing and proofreading processes, with respondents expressing high satisfaction with the support received from editors. Recommendations emphasize the importance of ongoing learning and the pursuit of additional resources to further refine these skills. Participants are encouraged to advocate for continued training programs within their institutions, with an appeal for administrative support to enhance professional development opportunities. The training not only equips educators with essential tools for academic advancement but also fosters a deeper understanding of research practices that benefit their students and the wider academic community. This study highlights the transformative potential of structured training programs in enhancing educational outcomes and promoting career growth.
Keywords: research writing; professional development; training programs; educational outcomes; career advancement